Photoelectric / colorimetric dual-mode sensor based on In2O3@FeMoSe2 composite material, preparation method and application thereof
The photoelectric/colorimetric dual-mode sensor constructed through In2O3@FeMoSe2 composite material solves the problems of cumbersome sample preparation and high detection limit for existing dopamine detection methods, and realizes high sensitivity and low detection limit for dopamine, which is suitable for the detection of human biological samples.
Patent Information
- Application Number
- CN202411995958.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-08
AI Technical Summary
The existing dopamine detection methods are complicated to process before sample preparation, require large instruments and complex operating steps, and have high detection limits and poor stability, making it difficult to meet practical application needs.
The photoelectric/colorimetric dual-mode sensor was constructed using In2O3@FeMoSe2 composite material, and the In2O3@FeMoSe2 composite material was prepared by hydrothermal method and modified on the conductive glass electrode for photoelectrochemical and colorimetric detection.
It has achieved high sensitivity and low detection limit (14.7nM) detection for dopamine, with good stability and selectivity, and is suitable for dopamine detection in human serum and urine.
Smart Images

Figure CN119780179A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of photoelectrochemical sensors, and in particular to a photoelectric / colorimetric dual-mode sensor based on an In2O3@FeMoSe2 composite material, a preparation method thereof and applications thereof. Background Art
[0002] Dopamine (DA) is an important neurotransmitter in the central nervous system known to humans, which can help human cells transmit various chemicals. The concentration range of dopamine is in dynamic balance in the human body, and there is a self-regulating mechanism with human mental stimulation. If the concentration is unbalanced, it may cause some very serious diseases, such as Parkinson's disease, Alzheimer's disease, and local ischemia in children. Therefore, it is very necessary to detect the content of dopamine in the human body and its concentration range. At present, the common methods for detecting DA mainly include high performance liquid chromatography (HPLC), capillary electrophoresis (CE) and ultraviolet spectrophotometry, but the sample preparation pretreatment of these methods is too troublesome, requiring large instruments and complicated operation steps. Photoelectrochemical (PEC) method is a method that has been used more in recent years. Among these methods, photoelectrochemical method has obvious advantages. This method has the advantages of low detection limit, good stability, wide detection range, more convenience, lower cost and short reaction time.
[0003] Indium oxide (In2O3) is a type of III-V semiconductor oxide with a large specific surface area, which can increase the effective area of gas adsorption and release, thereby showing excellent sensitivity. The surface is easy to functionalize and has extremely high mechanical stability. The electronic structure of its surface has a significant impact on its performance. Molybdenum diselenide (MoSe2) is a new type of semiconductor material with a unique electronic structure and high photoelectric conversion efficiency. It has potential application value in the field of optoelectronics. Due to the large interlayer spacing of MoSe2, some ions such as Fe 3+ and Li + It is easy to insert into the interlayer to form intercalation compounds, thereby regulating the electronic structure, increasing the density of catalytic active sites, improving its charge transfer conductivity and electrocatalytic activity, and is used in energy storage and the development of new functional materials. Iron-doped molybdenum diselenide (FeMoSe2) prepared by hydrothermal method can show a vertically arranged structure, which helps to expose more active edge sites, thereby improving electrocatalytic activity.
[0004] The present invention calcined the indium metal organic framework (In-MOF) to remove carbon and synthesize nano-stereoscopic In2O3, which has strong mechanical stability, good chemical stability and catalase-like properties. Taking advantage of the high electron mobility and good photoelectrochemical properties of FeMoSe2, a new In2O3@FeMoSe2 composite material was synthesized for the first time, so that the energy band gaps of the two overlapped to promote the transfer of electrons, improve the photoelectric conversion efficiency, and generate excellent photocurrent signals. Therefore, a colorimetric and photoelectrochemical sensing system was constructed based on this composite material, and the new dual-mode collaborative analysis system was applied to the detection of DA, using two different types of detection methods to generate different signals, further ensuring the accuracy of the test results. There is no related report yet. Summary of the invention
[0005] The purpose of the present invention is to provide a photoelectric / colorimetric dual-mode sensor based on In2O3@FeMoSe2 composite material, its preparation method and application in view of the above-mentioned problems. The constructed dual-mode sensor is suitable for detecting DA in human serum and urine, and has the advantages of lower detection limit, good stability, wide detection range, more convenience, lower cost and short response time.
[0006] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0007] First, a preparation method of a photoelectric / colorimetric dual-mode sensor based on an In2O3@FeMoSe2 composite material is provided, comprising the following steps:
[0008] (1) Preparation of In2O3@FeMoSe2
[0009] FeCl3·6H2O and Na2MoO4·2H2O were weighed and dissolved in deionized water to prepare a mixed solution A; selenium powder was weighed and dispersed and dissolved in hydrazine hydrate to prepare a mixed solution B, and then the mixed solution B was slowly dropped into the mixed solution A, black precipitate was continuously generated, and In2O3 was added after continuous stirring for a period of time, and the reaction was continued to be stirred to obtain a suspension; finally, the suspension was transferred to a polytetrafluoroethylene-lined reactor for hydrothermal reaction, and after the hydrothermal reaction was completed, it was cooled to room temperature, and the obtained black precipitate was washed with ethanol and deionized water, and then dried to obtain an In2O3@FeMoSe2 composite material, which was used as a material for constructing a colorimetric sensor and for the preparation of a photoelectrochemical sensor;
[0010] (2) Preparation of photoelectrochemical sensors
[0011] The ITO conductive glass electrode was cleaned and dried; the In2O3@FeMoSe2 composite material was weighed and ultrasonically dispersed in deionized water to obtain an In2O3@FeMoSe2 suspension; the In2O3@FeMoSe2 suspension was absorbed and coated on the conductive surface of the ITO glass electrode and dried naturally to obtain an In2O3@FeMoSe2 / ITO photoelectrochemical sensor.
[0012] In the above preparation method, preferably, the mass ratio of FeCl3·6H2O, Na2MoO4·2H2O and In2O3 is 1.0-1.2:1:0.5, and the molar ratio of Na2MoO4·2H2O and selenium powder is 1:1.8-2.1.
[0013] In the above preparation method, preferably, the reaction duration of adding the mixed solution B dropwise to the mixed solution A is 20 minutes.
[0014] In the above preparation method, preferably, the temperature of the hydrothermal reaction is 180±1° C., and the reaction time is more than 10 h.
[0015] In the above preparation method, preferably, the concentration of the In2O3@FeMoSe2 suspension is 1 mg / mL.
[0016] In the above preparation method, preferably, the coating amount of the In2O3@FeMoSe2 suspension is 10 μL.
[0017] The present invention also provides a dual-mode detection method for dopamine hydrochloride, that is, the electrochemical sensor prepared by the above preparation method is applied to the detection of dopamine hydrochloride.
[0018] Preferably, the detection of dopamine hydrochloride adopts a PEC-colorimetric dual-mode detection method, specifically:
[0019] (1) preparing a series of dopamine hydrochloride standard solutions with gradient concentrations;
[0020] (2) A three-electrode system was built using the In2O3@FeMoSe2 / ITO sensor as the working electrode, the Ag / AgCl electrode as the reference electrode, and the Pt electrode as the auxiliary electrode. A PBS solution was used as a buffer solution, and a dopamine hydrochloride standard solution was added to the buffer solution. Blue light was used as the excitation light source, and the potential was set to 0 V. The dopamine hydrochloride standard solution was detected by the current-time method to obtain a linear relationship between the photocurrent and the concentration of the dopamine hydrochloride standard solution;
[0021] (3) The peroxidase activity of the prepared enzyme-like material In2O3@FeMoSe2 was detected by colorimetry. The aqueous dispersion of TMB, the aqueous dispersion of H2O2, and the aqueous dispersion of In2O3@FeMoSe2 were respectively added to the citric acid-phosphate solution and mixed evenly to obtain a base solution. Multiple identical base solutions were prepared. Different concentrations of dopamine hydrochloride standard solutions were added to the base solution and incubated at room temperature for a period of time. The supernatant was then centrifuged and the ultraviolet-visible light absorbance was detected to obtain a linear relationship between the absorbance and the concentration of the dopamine hydrochloride standard solution.
[0022] (4) under the same conditions as step (2), adding the sample solution to be tested to the buffer solution, detecting the photocurrent response of the sample solution to be tested, and using the linear relationship obtained in step (2) to obtain the concentration of dopamine hydrochloride in the sample solution to be tested according to the measured photocurrent intensity; under the same conditions as step (3), adding the sample solution to be tested to the base solution, detecting the absorbance of the sample solution to be tested, and using the linear relationship obtained in step (3) to obtain the concentration of dopamine hydrochloride in the sample solution to be tested according to the measured absorbance.
[0023] In the above method, the incubation time is 20-40 min, preferably 30 min.
[0024] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0025] 1. The present invention synthesizes a novel In2O3@FeMoSe2 composite material for the first time, so that the energy band gaps of the two overlap, thereby promoting the transfer of electrons, improving the photoelectric conversion efficiency, and generating an excellent photocurrent signal. After the In2O3@FeMoSe2 composite material is modified on a conductive glass electrode and used as a PEC sensor for DA detection, DA acts as an electron donor to generate an enhanced photocurrent signal, thereby realizing the photoelectrochemical detection of DA. In the concentration range of 0.05μM to 100μM, the linear regression equation of photoelectric detection is I(nA)=3.34C(μM)+105.76(R=0.9982), and the detection limit is 14.7nM. At the same time, the overlapping of the band gap enhances the peroxidase activity of the material, catalyzing hydrogen peroxide to generate hydroxyl radicals, and then oxidizing 3,3',5,5'-tetramethylbenzidine (TMB) to blue oxide (TMBox), and generating a strong absorption peak at 651nm. Under the action of DA, it competes with TMB to react with hydroxyl radicals and inhibits the oxidation of TMB, thereby weakening the absorption peak intensity and gradually disappearing the blue color, realizing the colorimetric visualization detection of DA. In the concentration range of 0.5 to 75 μM, the linear regression equation of colorimetric detection is A = -0.0123C (μM) + 1.07 (R = 0.9970), and the detection limit is 0.19 μM. The PEC and colorimetric sensor based on In2O3@FeMoSe2 composite materials have a wide linear range and a low detection limit, which can realize dual-mode detection.
[0026] 2. The dual-mode sensor of the present invention has excellent stability, sensitivity and selectivity, stability and reproducibility, and a low detection limit. It is suitable for the practical application of detecting DA in human serum and urine, and is a universal, high-performance, economical and convenient PEC / colorimetric dual-mode detection platform. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 This is a SEM image of the material prepared in Example 1, wherein Figure 1 A and B are SEM images of In2O3; C and D are SEM images of In2O3@FeMoSe2; E and F are TEM images of In2O3@FeMoSe2;
[0028] Figure 2 This is the X-ray diffraction test result diagram of the material prepared in Example 1;
[0029] Figure 3 Photoelectric curves of different modified electrodes in PBS buffer solution without DA;
[0030] Figure 4 Photoelectric curves of different modified electrodes in PBS buffer solution containing DA;
[0031] Figure 5 EIS graphs of different modified electrodes;
[0032] Figure 6 UV-visible absorption spectra of different reaction systems (A) and the absorbance of each reaction system (B);
[0033] Figure 7 The photocurrent curves of different concentrations of DA (0.05-100 μM) (A) and their standard curves (B);
[0034] Figure 8 UV-visible spectra of different concentrations of DA (0-75 μM) (A) and their standard curves (B);
[0035] Fig. 9 This is the relationship diagram of the photocurrent ratio under the presence and coexistence of DA and interferents;
[0036] Fig.10 This is the absorbance ratio relationship diagram of DA and interfering substances alone and in coexistence;
[0037] Fig.11 The short-term stability test results of In2O3@FeMoSe2 / ITO in systems with and without DA. DETAILED DESCRIPTION
[0038] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] In the embodiments of the present invention, dopamine hydrochloride (DA), indium nitrate hydrate (In(NO3)3·xH2O), terephthalic acid (C8H6O4), ferric chloride hexahydrate (FeCl3·6H2O), and selenium powder (Se) were purchased from Shanghai Aladdin Reagent Co., Ltd., and hydrazine hydrate (N2H4·xH2O) was purchased from Chengdu Kelon Chemical Reagent Factory; 0.2 mol / L phosphate buffer solution (PBS) was prepared from NaH2PO4, Na2HPO4, and KCl; all reagents were of analytical grade; and the experimental water was deionized water.
[0040] All instrument models are as follows: EVO-18 scanning electron microscope and energy dispersive spectrometer (SEM, Carl Zeiss AG, Germany); Tecnai F20 transmission electron microscope (TEM, FEI Company, USA); D8 X-ray diffractometer (XRD, Bruker, Germany); Thermo K-Alpha X-ray photoelectron spectroscopy (XPS, Thermo Fisher Scientific, USA); KQ-300DB ultrasonic cleaning machine (Shanghai Yuezhong Instrument Equipment Co., Ltd.); UV-1601 ultraviolet-visible spectrophotometer (Shimadzu Corporation, Japan); photoelectrochemical reactor (blue light, Tianjin Aida Hengsheng Technology Development Co., Ltd.); CHI760E electrochemical workstation (Shanghai Chenhua Instrument Co., Ltd.).
[0041] In2O3 is prepared by hydrothermal synthesis. In the embodiment of the present invention, In2O3 is specifically prepared by the following method: weigh 1gC8H6O4 and 2.75g In(NO3)3·xH2O and disperse them in 315mL DMF, and stir and react at 100°C for 10min. After the suspension obtained after the reaction is cooled to room temperature, centrifuge (5000r / min) for 5min, wash 3 times with anhydrous methanol and anhydrous ethanol respectively, and obtain a white precipitate, which is dried in a vacuum drying oven at 40°C to obtain the precursor In-MOF. The dried In-MOF is placed in a tubular furnace, calcined in air at 120°C for 2h, and then calcined in air at 500°C for 2h, with a heating rate of 5°C / min, and then cooled to room temperature to obtain light yellow In2O3.
[0042] Example 1
[0043] The preparation method of the photoelectric / colorimetric dual-mode sensor based on the In2O3@FeMoSe2 composite material comprises the following steps:
[0044] (1) Preparation of In2O3@FeMoSe2
[0045] 0.2 g FeCl3·6H2O and 0.2 g Na2MoO4·2H2O were weighed and dissolved in 20 mL deionized water to prepare a mixed solution A; 0.12 g selenium powder was weighed and dispersed in 10 mL hydrazine hydrate (N2H4·xH2O) to prepare a mixed solution B, and then the mixed solution B was slowly added dropwise to the mixed solution A at a dropping speed of about 30 drops / min. At the same time, black precipitates were observed to be continuously generated. After continuous stirring for 20 min, 100 mg In2O3 was added, and the stirring reaction was continued for 1 h to obtain a suspension; finally, the suspension was transferred to a polytetrafluoroethylene-lined reactor, maintained at 180±1°C for 12 h, and a hydrothermal reaction was carried out. After the hydrothermal reaction was completed, it was cooled to room temperature, and the obtained black precipitate was washed 3 times with ethanol, and then washed 3 times with deionized water, and then vacuum dried at 45°C overnight to obtain a black powder In2O3@FeMoSe2;
[0046] (2) Preparation of photoelectrochemical sensors
[0047] The ITO (5×1cm, <6Ω) conductive glass electrode was ultrasonically cleaned with acetone and anhydrous ethanol for 20 minutes, ultrasonically cleaned with deionized water, and then dried with an infrared lamp for use; 1 mg of In2O3@FeMoSe2 composite material was weighed and ultrasonically dispersed in 1 mL of deionized water to obtain an In2O3@FeMoSe2 suspension with a concentration of 1 mg / mL; 10 μL of In2O3@FeMoSe2 suspension was applied to the conductive surface of the ITO glass electrode and dried naturally to obtain an In2O3@FeMoSe2 / ITO photoelectrochemical sensor.
[0048] Comparative Example 1 Preparation of In2O3 / ITO Electrode
[0049] 1 mg of In2O3 was weighed and ultrasonically dispersed in 1 mL of deionized water to prepare an In2O3 suspension with a concentration of 1 mg / mL; 10 μL of the In2O3 suspension was applied to the conductive surface of the ITO glass electrode and dried naturally to obtain an In2O3 / ITO electrode.
[0050] Comparative Example 2 Preparation of FeMoSe2 / ITO Electrode
[0051] 1 mg of FeMoSe2 was weighed and ultrasonically dispersed in 1 mL of deionized water to prepare a FeMoSe2 suspension with a concentration of 1 mg / mL; 10 μL of the FeMoSe2 suspension was applied to the conductive surface of the ITO glass electrode and dried naturally to obtain a FeMoSe2 / ITO electrode.
[0052] (I) Characterization of materials
[0053] The morphology of In2O3 and In2O3@FeMoSe2 composite materials was characterized by SEM and TEM. Figure 1 A and 1B are SEM images of In2O3, from which it can be observed that In2O3 is nanoparticles of uniform size. Figure 1 C and 1D are SEM images of the In2O3@FeMoSe2 composite material. It can be seen that the composite material has a petal-like structure, providing a large attachment area, and many In2O3 nanoparticles are attached to the surface. Figure 1 E and 1F are TEM images of In2O3@FeMoSe2 composite materials, showing that In2O3 is an elliptical nanosphere with a size of about 30nm. FeMoSe2 exhibits an ultra-thin sheet structure, providing a large surface area, thereby increasing the contact opportunity with the target molecule.
[0054] In2O3, FeMoSe2 and In2O3@FeMoSe2 composites were analyzed by XRD. Figure 2 , corresponding to lines a, b, and c, respectively, there are four characteristic peaks at 2θ=31.0°, 36.2°, 38.2°, and 51.1° of the In2O3@FeMoSe2 composite material, corresponding to the (222), (400), (411), and (440) crystal planes of In2O3; 2θ=28.5° and 34.7° correspond to the (100) and (103) crystal planes of FeMoSe2, respectively. These results indicate that In2O3 and FeMoSe2 have been successfully composited effectively.
[0055] (II) Performance testing
[0056] 1. Photocurrent response of different modified electrodes
[0057] In order to study the photoelectric conversion efficiency of different modified electrodes, each modified electrode was placed in a 0.2M PBS buffer solution (pH 7.0) using the I-t technique with an initial potential of 0V and a sampling interval of 0.5s to investigate the photoelectric response performance of the photoelectrode. Each modified electrode was a bare ITO electrode, an In2O3 / ITO electrode prepared in Comparative Example 1, a FeMoSe2 / ITO electrode prepared in Comparative Example 2, and an In2O3@FeMoSe2 / ITO electrode prepared in Example 1.
[0058] The results are as follows Figure 3 As shown, under ultraviolet light irradiation, bare / ITO (curve a) and In2O3 / ITO (curve b) have almost no photocurrent, while the photocurrent values of FeMoSe2 / ITO (curve c) and In2O3@FeMoSe2 / ITO (curve d) are 63.2nA and 100.8nA, respectively. The photocurrent of In2O3@FeMoSe2 / ITO is larger than that of the monomer electrode, indicating that the photoelectric conversion efficiency of In2O3@FeMoSe2 is higher.
[0059] In contrast, when 0.2 M PBS buffer solution (pH 7.0) contained 47.8 μM DA, Figure 4 As shown, there is still no obvious photocurrent change for bare / ITO (curve a) and In2O3 / ITO (curve b), the photocurrent values of FeMoSe2 / ITO (curve c) and In2O3@FeMoSe2 / ITO (curve d) are 124.2nA and 278.6nA, indicating that FeMoSe2 / ITO has a certain sensitivity to DA, while the photocurrent of In2O3@FeMoSe2 / ITO increases by 2.8 times under the influence of DA, indicating that In2O3@FeMoSe2 exhibits strong catalytic activity for DA.
[0060] 2. Electrochemical impedance spectroscopy (EIS) characterization of different modified electrodes
[0061] In order to explore the ability of electron transfer on the surface of different working electrodes, bare / ITO, In2O3 / ITO prepared in Comparative Example 1, FeMoSe2 / ITO prepared in Comparative Example 2 and In2O3@FeMoSe2 / ITO prepared in Example 1 were incubated in 5 mM [Fe(CN)6] 3- / 4- Electrochemical impedance spectroscopy (EIS) measurements were performed. The EIS parameter settings were: initial potential 0.35 V, interference amplitude 0.005 V, high frequency 10 4 Hz, low frequency is 1Hz, and the standing time is 2s.
[0062] The results are as follows Figure 5 As shown, In2O3 / ITO and FeMoSe2 / ITO have good conductivity, and the semicircle diameter is smaller than that of bare / ITO, showing strong electron transfer ability; In2O3@FeMoSe2 has the smallest diameter, and both In2O3 and FeMoSe2 have good electron transmittance and good conductivity. The two show a good synergistic effect, thereby accelerating the rate of electron transfer.
[0063] 3. Simulated peroxidase activity of different materials
[0064] In order to study the simulated peroxidase activity of different materials, TMB was selected as the colorimetric substrate of the reaction system, and the following groups of tests were carried out in the presence and absence of H2O2: Group a: 200 μL TMB (50 mM) and 100 μL In2O3@FeMoSe2 (1 mg / mL) aqueous dispersion were added to 1.5 mL citric acid-phosphate (0.1 M, pH 4.0) and mixed evenly; Group b: 200 μL TMB (50 mM) and 200 μL H2O2 (200 mM) aqueous dispersion were added to 1.5 mL citric acid-phosphate (0.1 M, pH 4.0) and mixed evenly; Group c: 200 μL TMB (50 mM), 200 μL H2O2 (200 mM), and 100 μL In2O3 (1 mg / mL) aqueous dispersion were added to 1.5 mL citric acid-phosphate (0.1 M, pH 4.0) and mixed evenly; Group d: 200μL TMB (50mM), 200μL H2O2 (200mM), 100μL FeMoSe2 (1mg / mL) aqueous dispersion were added to 1.5mL citric acid-phosphate (0.1M, pH 4.0) and mixed evenly; Group e: 200μL TMB (50mM), 200μL H2O2 (200mM), 100μL In2O3@FeMoSe2 (1mg / mL) aqueous dispersion were added to 1.5mL citric acid-phosphate (0.1M, pH 4.0) and mixed evenly. Test the absorbance of the base solution of each group.
[0065] The results are as follows Figure 6 shown. Figure 6 In A, in the absence of H2O2, TMB+In2O3@FeMoSe2 (curve a) has no obvious UV absorption, indicating that In2O3@FeMoSe2 is a peroxidase-like enzyme rather than an oxidase-like enzyme. In contrast, the three systems containing only H2O2 (curve b), In2O3-catalyzed H2O2 (curve c), and FeMoSe2 (curve d) all have low absorption, indicating that H2O2 alone or with monomers only slightly triggers the oxidation of TMB. When TMB, H2O2, and In2O3@FeMoSe2 are present at the same time, strong absorption intensity can be observed, accompanied by obvious color changes. Figure 6 As shown in Figure B, the absorption intensity of In2O3@FeMoSe2 is 1.7 and 2.0 times higher than that of In2O3 and FeMoSe2, respectively. These results indicate that In2O3@FeMoSe2 has excellent peroxidase activity.
[0066] Example 2 Dual-mode detection of dopamine hydrochloride
[0067] The electrochemical sensor prepared in Example 1 above was used to detect dopamine hydrochloride using a PEC-colorimetric dual-mode detection method, specifically:
[0068] (1) preparing a series of dopamine hydrochloride standard solutions with gradient concentrations ranging from 0.05 to 100 μM;
[0069] (2) A three-electrode system was constructed using the In2O3@FeMoSe2 / ITO sensor as the working electrode, the Ag / AgCl electrode as the reference electrode, and the Pt electrode as the auxiliary electrode. A pH 7.0, 0.2 mol / L PBS solution was used as a buffer solution. A dopamine hydrochloride standard solution was added to the buffer solution. Blue light (20 W) was used as the excitation light source. The potential was set to 0 V. The dopamine hydrochloride standard solution was detected using the current-time method to obtain a linear relationship between the photocurrent and the concentration of the dopamine hydrochloride standard solution. The results are as follows: Figure 7 As shown in A, as the concentration of DA increases, the photocurrent increases accordingly, showing a good positive correlation, and a good linear relationship is shown in the range of 0.05μM to 100μM ( Figure 7 B), the linear regression equation is I(nA)=3.34C(μM)+105.76(R=0.9982), and the detection limit is 14.7nM.
[0070] (3) The peroxidase activity of the prepared enzyme-like material In2O3@FeMoSe2 was detected by colorimetry. 200 μL TMB (50 mM), 200 μL H2O2 (200 mM), and 100 μL In2O3@FeMoSe2 (1 mg / mL) aqueous dispersion were added to 1.5 mL citric acid-phosphate (0.1 M, pH 4.0) and mixed evenly to obtain a base solution. Multiple portions of the same base solution were prepared, and different concentrations of dopamine hydrochloride standard solutions were added to the base solution and incubated at room temperature for 30 min. The supernatant was then centrifuged and the ultraviolet-visible absorbance was detected to obtain a linear relationship between the absorbance and the concentration of the dopamine hydrochloride standard solution. The results are shown in Figure 2. Figure 8 As shown in A, it can be seen that the absorbance of TMBox at 651 nm decreases with the increase of DA concentration, and shows a good linear relationship in the range of 0.5 to 75 μM ( Figure 8 B), the linear regression equation is A=-0.0123C(μM)+1.07(R=0.9970), and the detection limit is 0.19μM.
[0071] (4) under the same conditions as step (2), adding the sample solution to be tested to the buffer solution, detecting the photocurrent response of the sample solution to be tested, and using the linear relationship obtained in step (2) to obtain the concentration of dopamine hydrochloride in the sample solution to be tested according to the measured photocurrent intensity; under the same conditions as step (3), adding the sample solution to be tested to the base solution, detecting the absorbance of the sample solution to be tested, and using the linear relationship obtained in step (3) to obtain the concentration of dopamine hydrochloride in the sample solution to be tested according to the measured absorbance.
[0072] (I) Selectivity, reproducibility and stability
[0073] Selectivity is a key factor in evaluating the analytical performance and practicality of the dual-mode assay platform. In order to study the selectivity of the prepared sensor, cations (including Ca 2+ Mg 2+ 、Na + and K + ), uric acid (UA), glucose (Glu), glycine (Gly), arginine (Arg), L-cysteine (Cys), glutathione (GSH), ascorbic acid (AA), etc., which may exist in human serum and urine, are introduced into PEC and colorimetric sensing experiments, which is equivalent to 50 times the concentration of DA. The materials and sensors prepared in Example 1 and the method in step (4) of Example 2 are used to test the photocurrent intensity and absorbance of each group of test liquids, and the photocurrent ratio and absorbance ratio are calculated, wherein the photocurrent ratio = the photocurrent intensity when DA and the interferent coexist / the photocurrent intensity when only DA is present, and the absorbance ratio = the absorbance when DA and the interferent coexist / the absorbance when only DA is present. The results are as follows: Fig. 9 and 10 As shown, the presence of interferents had little effect on the signals of PEC and colorimetric assays, indicating that the proposed dual-mode sensor has good selectivity.
[0074] Three different concentrations of DA (5, 30 and 60 μM) were used to evaluate the reproducibility of the sensor. Using the materials and sensors prepared in Example 1 and the method in step (4) of Example 2, the photocurrent intensity and absorbance at different concentrations of DA were tested, and the test concentration was calculated. At three different concentrations, the relative standard deviations (RSD1) of the colorimetric sensor were 2.41, 1.87 and 2.10%, respectively, and the RSD2 of the PEC sensor were 1.77, 1.94 and 1.11%, respectively, indicating that the sensor has good reproducibility.
[0075] In addition, the stability of In2O3@FeMoSe2 / ITO in the presence (30 μM) or absence of DA was studied. According to the method in Example 1, an In2O3@FeMoSe2 / ITO sensor was constructed to observe its short-term stability. The light was turned on / off once every 50 seconds and repeated 20 times to test its photocurrent intensity. Fig.11 As shown, the RSDs are 0.33% and 0.74% respectively, indicating that the designed PEC sensor has high short-term stability. After the electrode was stored at 4°C for 1 month, the DA was measured under the same conditions, and the current value obtained was 91% of the initial peak current value, indicating that the sensor has good long-term stability.
[0076] (II) Testing of actual samples
[0077] Under the conditions of Example 2, the DA content in human blood and urine samples was determined by spike recovery based on PEC and colorimetric sensor. The results are shown in Table 1.
[0078] Table 1. Detection results of DA in human serum and urine samples (N=3)
[0079]
[0080]
[0081] The recoveries of DA at three spiked levels were 100.80%-102.7% and 95.88%-98.48%, and the RSDs were 1.56%-3.51% and 1.88%-3.10%, respectively, indicating that the detection results of this method are reliable and can be applied to the detection of DA content in biological samples.
[0082] The above description is a detailed description of the preferred feasible embodiments of the present invention, but the embodiments are not intended to limit the scope of the patent application of the present invention. All equivalent changes or modified changes completed under the technical spirit suggested by the present invention should fall within the patent scope covered by the present invention.
Claims
1. A method for preparing a photoelectric / colorimetric dual-mode sensor based on In2O3@FeMoSe2 composite material, characterized in that: The following steps are involved: (1) Preparation of In2O3@FeMoSe2 FeCl3·6H2O and Na2MoO4·2H2O were weighed and dissolved in deionized water to prepare a mixed solution A; selenium powder was weighed and dispersed and dissolved in hydrazine hydrate to prepare a mixed solution B, and then the mixed solution B was slowly dropped into the mixed solution A, black precipitate was continuously generated, and In2O3 was added after continuous stirring for a period of time, and the reaction was continued to be stirred to obtain a suspension; finally, the suspension was transferred to a polytetrafluoroethylene-lined reactor for hydrothermal reaction, and after the hydrothermal reaction was completed, it was cooled to room temperature, and the obtained black precipitate was washed with ethanol and deionized water, and then dried to obtain an In2O3@FeMoSe2 composite material, which was used as a material for constructing a colorimetric sensor and for the preparation of a photoelectrochemical sensor; (2) Preparation of photoelectrochemical sensors The ITO conductive glass electrode is cleaned and dried; the In2O3@FeMoSe2 composite material is weighed and ultrasonically dispersed in deionized water to obtain an In2O3@FeMoSe2 suspension; the In2O3@FeMoSe2 suspension is absorbed and coated on the conductive surface of the ITO glass electrode, and dried naturally to obtain In2O3@FeMoSe2 / ITO, that is, a photoelectrochemical sensor.
2. The preparation method according to claim 1, characterized in that: The mass ratio of the FeCl3·6H2O, Na2MoO4·2H2O and In2O3 is 1.0-1.2:1:0.5, and the molar ratio of the Na2MoO4·2H2O and selenium powder is 1:1.8-2.
1.
3. The preparation method according to claim 1, characterized in that: The reaction time of adding the mixed solution B dropwise to the mixed solution A is 20 minutes.
4. The preparation method according to claim 1, characterized in that: The temperature of the hydrothermal reaction is 180±1° C., and the reaction time is more than 10 hours.
5. The preparation method according to claim 1, characterized in that: The concentration of the In2O3@FeMoSe2 suspension is 1 mg / mL.
6. The preparation method according to claim 1, characterized in that: The coating amount of the In2O3@FeMoSe2 suspension is 10 μL.
7. The photoelectrochemical sensor prepared according to the preparation method according to any one of claims 1 to 6.
8. Use of the photoelectric / colorimetric dual-mode sensor prepared according to the preparation method according to any one of claims 1 to 6 in detecting dopamine hydrochloride.
9. The use according to claim 8, characterized in that The detection of dopamine hydrochloride adopts a photoelectric-colorimetric dual-mode detection method, specifically: (1) preparing a series of dopamine hydrochloride standard solutions with gradient concentrations; (2) A three-electrode system was built using the In2O3@FeMoSe2 / ITO sensor as the working electrode, the Ag / AgCl electrode as the reference electrode, and the Pt electrode as the auxiliary electrode. A PBS solution was used as a buffer solution, and a dopamine hydrochloride standard solution was added to the buffer solution. Blue light was used as the excitation light source, and the potential was set to 0 V. The dopamine hydrochloride standard solution was detected by the current-time method to obtain a linear relationship between the photocurrent and the concentration of the dopamine hydrochloride standard solution; (3) The peroxidase activity of the prepared enzyme-like material In2O3@FeMoSe2 was detected by colorimetry. The aqueous dispersion of TMB, the aqueous dispersion of H2O2, and the aqueous dispersion of In2O3@FeMoSe2 were respectively added to the citric acid-phosphate solution and mixed evenly to obtain a base solution. Multiple identical base solutions were prepared. Different concentrations of dopamine hydrochloride standard solutions were added to the base solution and incubated at room temperature for a period of time. The supernatant was then centrifuged and the ultraviolet-visible light absorbance was detected to obtain a linear relationship between the absorbance and the concentration of the dopamine hydrochloride standard solution. (4) under the same conditions as step (2), adding the sample solution to be tested to the buffer solution, detecting the photocurrent response of the sample solution to be tested, and using the linear relationship obtained in step (2) to obtain the concentration of dopamine hydrochloride in the sample solution to be tested according to the measured photocurrent intensity; under the same conditions as step (3), adding the sample solution to be tested to the base solution, detecting the absorbance of the sample solution to be tested, and using the linear relationship obtained in step (3) to obtain the concentration of dopamine hydrochloride in the sample solution to be tested according to the measured absorbance.
10. The use according to claim 9, characterized in that: The incubation time is 30 min.